Correlation between increased neutrophil gelatinase-associated lipocalin urine protein level with disease activities on pediatrics lupus nephritis: A meta-analysis study - Vitariana, Ade Ratna Ayu; Prasetyo, Risky Vitria; Wungu, Citrawati Dyah Kencono (Edelweiss Applied Science and Technology, 2024)
This study aims to evaluate the correlation between urinary Neutrophil Gelatinase-Associated Lipocalin (NGAL) levels and disease activity in pediatric lupus nephritis, emphasizing its role as a potential biomarker. A systematic review and meta-analysis were conducted on observational studies (cross-sectional, cohort, and case-control) sourced from PubMed, Science Direct, Scopus, and Web of Science, covering publications up to March 2024. The Newcastle-Ottawa Scale was used to assess study quality, and data analysis was performed using Review Manager 5.4 and STATA SE 16. Pooled correlation values were calculated using a fixed-effects model. The meta-analysis included nine studies involving pediatric patients. Results indicated a significant positive correlation between urinary NGAL levels and lupus nephritis disease activity on pediatrics, with a pooled Fisher’s z of 0.4 (95% CI 0.34–0.46) and a pooled correlation coefficient of 0.380 (95% CI 0.327–0.430; p < 0.05). Publication bias was minimal, as shown by Egger’s test (p > 0.05) and a symmetrical funnel plot. Sensitivity analysis confirmed the robustness of the findings. The study demonstrates that urinary NGAL is a reliable biomarker for assessing disease activity in pediatric lupus nephritis, offering a non-invasive method for monitoring disease progression. These findings have significant clinical relevance, supporting the integration of urinary NGAL measurement into routine practice for early detection and management of lupus nephritis flares in children, thereby improving patient outcomes through timely intervention.